Enhancing Occupational Safety Performance through the Implementation of UCAD in Drilling and Well Intervention Operations - Helmi Indra Fauzi; Nur Rokhman (Jurnal KESANS : Kesehatan dan Sains, 2026)
Introduction: The oil and gas industry carries high operational risks, particularly in drilling and well intervention activities, where incidents such as near misses continue to occur despite existing safety systems Objective: This study evaluates the implementation of the Upgrading Competency and Awareness Database (UCAD) system in mitigating risks within drilling and well intervention operations Method: A qualitative descriptive case study approach was employed, utilizing field observations, technical document reviews, and in-depth interviews with safety officers and operational personnel. Result and Discussion: The UCAD system implementation was categorized as poor, with a compliance rate of 38.5%. Significant gaps were identified in data utilization, personnel participation, and well control competency. Critical areas requiring improvement include inspections of well control equipment, dropped objects, hoisting systems, and pressurized systems. Conclusions: Cumulative participation in the program has not yet been achieved, and improvements are required in both system implementation and personnel competency development. Strengthening technical training and enhancing supervision are essential to prevent major accident hazards and to improve over all safety performance in drilling and well intervention operations.